Is There a Role of Meniscal Morphology in the Risk of Noncontact Anterior Cruciate Ligament Rupture? A Case–Control Study - Unal, Melih; Kose, Ozkan; Aktan, Cemil; Gumussuyu, Gurkan; May, Hasan; Kati, Yusuf Alper (The Journal of Knee Surgery, 2020)
The purpose of this study was to identify the anatomical risk factors and determine the role of meniscal morphology in noncontact anterior cruciate ligament (ACL) rupture. A total of 126 patients (63 with noncontact ACL rupture and 63 age- and sex-matched controls) with intact menisci were included in this retrospective case–control study. On knee magnetic resonance imaging (MRI), meniscal morphometry (anterior, corpus, and posterior heights and widths of each meniscus), tibial slope (medial and lateral separately), notch width index, roof inclination angle, anteromedial bony ridge, tibial eminence area, and Q-angle measurements were assessed. The data were analyzed using multiple regression analyses to identify independent risk factors associated with ACL rupture. Using a univariate analysis, medial and lateral menisci anterior horn heights (p < 0.001; p < 0.003), medial and lateral menisci posterior horn heights (p < 0.001; p < 0.001), lateral meniscus corpus width (p < 0.004), and notch width index (p < 0.001) were significantly higher in the control group. Lateral tibial slope (p < 0.001) and anteromedial bony ridge thickness (p < 0.001) were significantly higher in the ACL rupture group. Multivariate analysis revealed that decreased medial meniscus posterior horn height (odds ratio [OR]: 0.242; p < 0.001), increased lateral meniscus corpus width (OR: 2.118; p < 0.002), increased lateral tibial slope (OR: 1.95; p < 0.001), and decreased notch width index (OR: 0.071; p = 0.046) were independent risk factors for ACL rupture. Notch stenosis, increased lateral tibial slope, decreased medial meniscus posterior horn height, and increased lateral meniscus corpus width are independent anatomical risk factors for ACL rupture. Meniscal morphological variations also play a role in ACL injury. This is a Level III, retrospective case–control study.
Keywords: anterior cruciate ligament; injury; meniscus; morphology; risk factors